Non-pecuniary Value of Employment and Individual Labor Supply - Y. Hossein Farzin; Ken-Ichi Akao (Fondazione Eni Enrico Mattei (FEEM), 2004)
Recognizing that people value employment not only to earn income to satisfy their consumption needs but also as a means of community involvement that provides socio-psychological (non-pecuniary) benefits, we show that once the non-pecuniary benefits of employment are incorporated in the standard individuals utility function, then at very low income levels employment can be a source of utility, inducing individuals to supply labor to the extent possible. We also show the conditions under which a greater non-pecuniary effect of employment generates a larger individual labor supply.
Keywords: D62; J22; I31; 330; Non-pecuniary effects; Employment value; Labor supply; Arbeitsangebot; Erwerbstätigkeit; Theorie